The Asian financial crisis and the policy responses / Noorain Omar ...[et al.] - Omar, Noorain; Saad, Ramli; Abdullah, Mohd Zulhelmey (Universiti Teknologi MARA, Kedah, 2013)
The severe economic slowdown and monetary crisis that affected most Asian countries after massive speculative activity forced the devaluation of the Thai baht in July 1997. Many other currencies in the region came under heavy pressure from speculators, forcing interest rates to rise, while asset values fell as money flowed out of Asia. Banking systems came under enormous pressure, with bad debt levels rising sharply. The crisis lasted through 1998, but growth remained weak until the Internet boom began to take hold in 1999-2000. The deflationary impact of the Asian financial crisis could still be felt until economies began a sustained recovery in 2003. The objective of this paper is therefore to provide a snap shot of the 1997 financial crisis in Asia, how it was tackled by different governments in the region and most importantly, the lessons that can be learnt from it.